Genotipificación del Virus del Papiloma Humano(VPH) en muestras de cepillados cervicales de pacientes de diferentes hospitales de Bogotá y evaluación de la concordancia de dos métodos basados en PCR Genotyping the human papilloma virus (HPV) in Cytobrush samples taken from patients attending different hospitals in Bogotá (Colombia) and evaluating agreement between two PCR-based methods - Dabeiba A García; Markus Schmitt; Ángel Cid-Arregui; Marcos Castillo; Ignacio Briceño; Fabio A Aristizábal (Federación Colombiana de Obstetricia y Ginecología, 2010)
Objetivo: genotipificar el VPH en muestras de pacientes con diferentes grados histopatológicos de lesión cervical. Materiales y métodos: estudio de corte transversal en muestras de cepillado cervical de mujeres con diferentes grados de lesiones cervicales histopatológicas en la ciudad de Bogotá en el año 2009. Se utilizó Luminex® xMAP® una técnica altamente sensible, reproducible y automatizada, y Reverse Line Blot (RLB). Resultados: las infecciones por los tipos de VPH de 16 y 18 fueron las más frecuentes en todos los tipos de patología del cérvix. Las infecciones mixtas predominaron con un 78,04% de los casos con patología negativa, 85,7% NIC I, 81,25% NIC II, 78,78% NIC III y 71,42% cáncer cervical. La concordancia entre los dos métodos fue del 67%. Conclusión: las infecciones por los tipos de VPH 16 y 18 predominan en la población estudiada. Objective: genotyping HPV in samples taken from patients having different histopathological degrees of cervical injury. Materials and methods: this was a cross-sectional study of cervical scrape samples taken from females having different degrees of histopathological cervical injury in Bogotá during 2009. Luminex® xMAP® was used, which is a highly sensitive, reproducible and automated technique, as well as reverse line blot (RLB). Results: infections caused by HPV types 16 and 18 were the most frequently found types of pathology of the cervix. Mixed infections predominated (78.04%); amongst cases having negative pathology, 85.7% was found for cervical intraepithelial neoplasia (CIN) I, 81.25% for CIN II, 78.78% for CIN III and 71.42% for cervical cancer. Agreement between both methods was 67%. Conclusion: infection by VPH types 16 and 18 predominated in the population being studied.